Digital and Clinical evaluation of temporomandibular disorders in full dentition and free end extension patients. (Mustansiria Dental Journal, 2023)
Background: Temporomandibular disorders (TMD) Which are a subgroup of craniofacial pain disorders involving chronic pain, dysfunction of the temporomandibular joint (TMJ), masticatory muscles and associated musculoskeletal structures of the head and neck. Pain is one of the most frequent clinical features for these TMD in addition to the clicking, limitation of mouth opening and deviation. This study aimed to evaluate Digital evaluation of the occlusal instability parameters (Disclusion Time, Occlusion Time, trajectory of force Index and Occlusal Interferences).Method:  the study including 180 patients with free end extension and full dentition (kennedy classification class I and II) their age was between (20-50) years old .they had either disc displacement or myofascial pain dysfunction syndrome according to shiffman criteria.and also examined by digital T scan.Result: the result showed significant pain difference between free end extension and full dentition patients. Conclusion: The trajectory of force distribution is highly variable between the two major groups, the full dentition exhibit more posterior force while The free end patients tend to establish more anterior force which lead to a series of temporomandibular disorders.